Sengketa Pemilihan Kepala Desa Serentak: Studi Kasus di Kabupaten Luwu Utara - La Ode Husen; Abd. Kahar Muzakkir; Nasirah Nasirah (Al-Ishlah: Jurnal Ilmiah Hukum, 2021)
This study aims to describe the simultaneous Village Head election disputes in 2016 and 2018 in North Luwu Regency. This research combines normative juridical and empirical research methods. The primary data were collected using direct interviews, while the secondary data was collected using literature study techniques. The data obtained in this research were then analyzed qualitatively to describe problems and answer study purposes. The results show the implementation of the simultaneous Village Head election of 2016 and 2018 in North Luwu Regency, consisting of 64 Villages. Of the 64 simultaneous Village Head elections, six of them are still considered to contain legal defects by several candidates. Accordingly, the six candidates submitted lawsuits against the simultaneous Village Head election results at the State Administrative Court to prove the violation. In this case, there are two lawsuits for Regent Decision No. 188.4.45/386/VI/2016 and four for Regent Decision No. 188.4.45/479/XI/2018. One of the six lawsuits was granted by the Judge in the Decision of the State Administrative Court, but the Decision of the State Administrative High Court voided the Court Decision of the first instance. In contrast, the other five lawsuits were immediately dismissed by the Judge at the Decision of the State Administrative Court. Therefore, it is recommended that the Regency Government be able to predict and provide solutions to a series of problems that will arise at all stages of implementing the simultaneous Village Head election. In this case, to minimize future disputes of the simultaneous Village Head election.